When the medium is war: Marshall McLuhan, media, and militarisation. Issue 9 (2nd September 2021) - Deer, Patrick
ABSTRACT: This essay explores Marshall McLuhan's argument in War and Peace in the Global Village that 'the first television war' of Vietnam was staged in a new technological 'medium' that reduced viewers' capacity for critical distance, blurred divisions between civilians and soldiers, undercutting the war's domestic legitimacy and painfully shattering the 'old image' of national identity. Considering postcolonial critiques of McLuhan's reliance on ethnopsychiatrist, J.C. Carothers, I explore the critical potential of his textual citations of Fanon, Joyce's Finnegans Wake, J.K. Galbraith, and the satirical hoax, Report from Iron Mountain, and of Quentin Fiore's graphic designs. Extending McLuhan's arguments to the US military's 2003 Iraq war media embedding programme, I argue that although they sought to avoid the uncontrolled media reporting of Vietnam, the war planners were nevertheless subject to the same destabilising 'invisible environments of technological innovation'. McLuhan's discussion of the ways technological innovation destabilises identities and promotes a violent quest to recover 'old images' of personal and national identity thus suggests that post-Vietnam war planners may have drastically overestimated the power of metaphorical and narrative framing when applied to media spectacle of war.